Development of handmade screen-printed electrode with conductive ink containing CuO-ZnO and N-doped graphene for electrochemical determination of dopamine - Kurteli, Rabianur; Dokur, Ebrar; Uruc, Selen; Gorduk, Ozge; Sahin, Yucel (ELSEVIER, 2025)
As people's living standards increase, the need for flexible and wearable sensors is growing in parallel with the increasing interest in flexible sensor for monitoring human health. Dopamine plays a crucial role in both the cardiovascular and central nervous systems. The development of reliable sensors for determining dopamine is crucial for understanding various biological processes and mechanisms. This study presents a new and adaptable screen-printed electrode (SPE) for dopamine monitoring using an innovative hybrid conductive ink. The conductive fillers were composed of a hybrid material of CuO-ZnO and N-doped graphene (N-Gr) composites. A handmade screen-printed electrode (SPE) was prepared by integrating hybrid conductive ink into paper substrates. The investigation focused on the production process and composition of the ink to produce disposable electrodes that exhibit high electrical conductivity and strong integration into the paper substrate. Dopamine detection was electrochemically performed using the Graphite/N-doped graphene/CuO-ZnO hybrid material/ SPE (G/N-Gr/CuO-ZnO/SPE). The electrode's linear range was 0.25-750 mu M, with a limit of detection (LOD) of 0.095 mu M. The results show that the developed electrode is effective in the detection of dopamine due to its ease of fabrication, low cost and electroanalytical properties.
Keywords: Conductive ink; Flexible; Paper electrode; Screen printed electrode; Dopamine; SELECTIVE DETECTION; ASCORBIC-ACID; URIC-ACID; SENSOR; NANOCOMPOSITE; PERFORMANCE; SUBSTRATE; Materials Science